Role of tumor cell senescence in non-professional phagocytosis and cell-in-cell structure formation - Gottwald, Dorian; Putz, Florian; Hohmann, Nora; Büttner-Herold, Maike; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (BMC Molecular and Cell Biology, 2020)
Background: Non-professional phagocytosis is usually triggered by stimuli such as necrotic cell death. In tumor therapy, the tumors often disappear slowly and only long time after the end of therapy. Here, tumor therapy inactivates the cells by inducing senescence. Therefore, study focused whether senescence is a stimulus for non-professional phagocytosis or whether senescent cells themselves phagocytize non-professionally. Results: Senescence was induced in cell lines by camptothecin and a phagocytosis assay was performed. In tissue of a cohort of 192 rectal cancer patients senescence and non-professional phagocytosis was studied by anti-histone H3K9me3 and anti-E-cadherin staining. Senescent fibroblasts and pancreas carcinoma cells phagocytize necrotic cells but are not phagocytized. In the tissue of rectal carcinoma, senescent cells can phagocytize and can be phagocytized. A high number of senescent cells and, at the same time, high numbers of non-professional phagocytizing cells in the rectal carcinoma tissue lead to an extremely unfavorable prognosis regarding overall survival. Conclusion: Senescent cells can be non-professionally phagocytized and at the same time they can non-professionally phagocytize in vivo. In vitro experiments indicate that it is unlikely that senescence is a strong trigger for non-professional phagocytosis. Combined high rates of non-professional phagocytosis and high rates of senescence are an extremely poor prognostic factor for overall survival.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Camptothecin; Cannibalism; Cell-in-cell; Entosis; Non-professional phagocytosis; Prognostic factor and survival; Rectal cancer; Senescence